2002
DOI: 10.1523/jneurosci.22-24-10524.2002
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Ca2+Entry Is Unchanged during Hippocampal Mossy Fiber Long-Term Potentiation

Abstract: The hippocampal mossy fiber (MF)-CA3 synapse exhibits NMDA receptor-independent long-term potentiation (LTP), which is expressed by presynaptic mechanisms leading to persistent enhancement of transmitter release. Recent studies have identified several molecules that may play an important role in MF-LTP. These include Rab3A, RIM1alpha, kainate autoreceptor, and hyperpolarization-activated cation channel (I(h)). However, the precise cellular expression mechanism remains to be determined because some studies noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 35 publications
5
50
2
Order By: Relevance
“…Furthermore, previous study demonstrated that forskolin, which raise intracellular cyclic AMP levels and reportedly cause mossy fiber synaptic enhancement (Weisskopf et al, 1994), didn't affect F value significantly (Kamiya et al, 2002).These results exclude the possibility that caffeine-induced presynaptic Ca 2+ increase involves inhibiting effects of caffeine on A1 receptors and phosphodiesterase. Instead, Ca 2+ release from presynaptic ryanodine-sensitive stores likely mediates the action of caffeine.…”
mentioning
confidence: 75%
“…Furthermore, previous study demonstrated that forskolin, which raise intracellular cyclic AMP levels and reportedly cause mossy fiber synaptic enhancement (Weisskopf et al, 1994), didn't affect F value significantly (Kamiya et al, 2002).These results exclude the possibility that caffeine-induced presynaptic Ca 2+ increase involves inhibiting effects of caffeine on A1 receptors and phosphodiesterase. Instead, Ca 2+ release from presynaptic ryanodine-sensitive stores likely mediates the action of caffeine.…”
mentioning
confidence: 75%
“…21), we cannot exclude other possibilities, such as a direct link between I h channels and some factor(s) downstream from Ca 2ϩ (21)(22)(23)(24). In addition, although the 30-s hyperpolarization is sufficient to induce AP-induced facilitation of cell secretion, it is not clear whether such hyperpolarization occurs in DRG neurons in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…One report postulates that I h is responsible for cAMP-dependent LTP because the I h antagonist ZD7288 blocks the LTP (22) whereas two other reports argue that the block could be due to side-effects of ZD7288 so I h is not involved in LTP (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6J mice and Wistar rats were used in the present study, and treated according to the guidelines for the care and use of laboratory animals of Hokkaido University School of Medicine. Transverse hippocampal slices of 400 m thick were prepared from 4-to 20-d-old mice and rats as described previously (Kamiya et al, 2002). In this study, we denoted mice of age P14 -P20 as "juvenile" mice, and those of age P4 -P6 as "neonatal" mice.…”
Section: Methodsmentioning
confidence: 99%